FILOLOGI SEBAGAI ILMU BANTU SEJARAH: TELAAH TEORITIS-PRAKTIS - Arditya Prayogi (SWADESI: Jurnal Pendidikan dan Ilmu Sejarah, 2021)
In general, philology is the study of various things contained in old texts. On the other hand, the science of history is the study of events in the past. The relationship between the two (including with other sciences) is reciprocal and requires each other. This article aims to describe theoretically and practically, the position of philology as an auxiliary science for other sciences. In addition, it also tries to discuss how philology is specifically used by the science of history as a science to help in uncovering various historical events that occurred in the past. This article was written using a descriptive analytic method with a qualitative approach, as well as literature research. In this article, it can be seen that the position of philology as an auxiliary science is realized by its function as a science that is able to process the content of manuscripts and texts to be easier to study, where philology provides text edits that can be used by various sciences based on the remains of the past. In relation to the science of history, philology helps to study the remains of the past in the form of manuscripts which are one of the historical sources.